The Official Conceptualization of the anti-Armenian Riots of 1895-1897 - Edip Gölbaşı (Études Arméniennes Contemporaines, 2018)
This paper examines the official terminology, representations, and narratives regarding the origins and nature of the anti-Armenian riots of 1895-1897. Official language provides evidence useful in understanding the ways in which the government authorities conceptualized and responded to these events. It suggests that through the constant use of the passive voice and euphemistic statements, the imperial authorities sought to neutralize the violence committed against a particular segment of the population and tried to conceal the agency of perpetrators in the mass killing of Ottoman Armenians. The official narrative—or the deployment of the concept of provocation as a direct explanation for violence—did not simply arm the Ottoman authorities with a rhetoric they could effectively use for domestic and international consumption, but it also freed them from moral responsibility and the punishment of perpetrators. Narratives of provocation also raised a host of significant questions about causality, accountability, and victimhood.